meta-Selective olefination of fluoroarenes with alkynes using CO2 as a traceless directing group - Spencer, Andrew R. A.; Korde, Rishi; Font, Marc; Larrosa, Igor (Chemical science (Cambridge), 2020)
Over the last few decades C-H olefination has received significant interest, due to the importance and usefulness of aryl olefins both as synthetic targets and intermediates. While a wide range of ortho-olefination protocols have been developed, only a small number of meta-olefinations are currently available. Importantly, the most common approach to meta-olefination, using a large meta-directing template, is not suitable for substrates such as fluorobenzenes, which cannot be derivatised. We report that the meta-selective olefination of fluoroarenes can be achieved via the use of CO2 as a traceless directing group, which can be easily installed and removed in a one-pot process. Furthermore, this approach avoids the use of stoichiometric Ag(i)-salts, commonly used in C-H olefinations, and affords complete meta- over ortho/para-regioselectivity.